Criminalidade e indicadores socioeconômicos no Estado de Minas Gerais (MG) - Juliana Nobre Canela (2021)
The State of Minas Gerais (MG) has significant crime rates. The spatial distribution of the rates of crimes against property, against a person, with the use of firearms, related to drug trafficking and also crimes of less offensive potential among the municipalities of Minas Gerais is quite heterogeneous. This research aims to study crime in the state of Minas Gerais and the influence of socioeconomic factors, in the year 2019. Therefore, a theoretical support was used, searching in Criminology, criminological theories that could explain criminality, either in the Consensus or Functionalist or Integration Theories or in the conflict or argumentative theories. The Multivariate Statistical Technique of Factor Analysis was applied. Based on the results obtained, maps were made. We used databases from João Pinheiro’s Foundation (Mineiro Social Responsibility Index - IMRS); from the Brazilian Institute of Geography and Statistics - IBGE; from the Civil and Military Police of the State of Minas Gerais; from the Integrated Center for Social Defense Information – CINDS, and geo-prisons from the National Council of Justice. With regard to the results, it was observed that the indicators used contribute to the occurrence and incidence of crime, leading to the conclusion that crimes against property are more common in more developed regions; on the other hand, crimes against a person tend to have less influence from socioeconomic factors. As for the population, it was observed that environments with higher concentrations of people tend to have greater ease of escape and difficulties in identifying the criminal. The larger the population, the greater the number of crime occurrences. Poverty and misery are not fundamental for an individual to become a criminal, but if associated with other factors, they can influence criminality.